Post-COVID fungal osteomyelitis-Another killer - Surender Pal Singh Sodhi; Gursimrat Kaur Brar; Deepinder Pal Singh Sodhi; Gurmeet Singh Brar; Sonu Gupta; Mehak Malhotra (Wolters Kluwer Medknow Publications, 2023)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been sweeping across the globe as a pandemic. Based on a retrospective analysis of SARS data from worldwide, it is summarized that the fungal co-infections associated with global COVID-19 might be missed or misdiagnosed. Along with, we report case series of fungal infections in the maxilla and in the orbit, who were successfully treated for covid-19 and are on regular follow-up.